2020
DOI: 10.1099/ijsem.0.004263
|View full text |Cite
|
Sign up to set email alerts
|

Cupriavidus agavae sp. nov., a species isolated from Agave L. rhizosphere in northeast Mexico

Abstract: During the isolation of bacteria from the Agave L. rhizosphere in northeast Mexico, four strains with similar BOX-PCR patterns were collected. The 16S rRNA gene sequences of all four strains were very similar to each other and that of the type strains of Cupriavidus metallidurans CH34T (98.49 % sequence similarity) and Cupriavidus necator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The genus Cupriavidus includes 19 validly published taxa, with C. necator reported as the type species [3], including the most recently described species, Cupriavidus agavae [4]. Cupriavidus species are found in the soil, rhizosphere and in human clinical specimens, particularly in samples obtained from debilitated patients [1, 4–9].…”
Section: Full-textmentioning
confidence: 99%
See 2 more Smart Citations
“…The genus Cupriavidus includes 19 validly published taxa, with C. necator reported as the type species [3], including the most recently described species, Cupriavidus agavae [4]. Cupriavidus species are found in the soil, rhizosphere and in human clinical specimens, particularly in samples obtained from debilitated patients [1, 4–9].…”
Section: Full-textmentioning
confidence: 99%
“…The genus Cupriavidus was first proposed in 1987 by Makkar and Casida, who described a non-obligate bacterial predator in soil, named Cupriavidus necator N-1 T [2]. The genus Cupriavidus includes 19 validly published taxa, with C. necator reported as the type species [3], including the most recently described species, Cupriavidus agavae [4]. Cupriavidus species are found in the soil, rhizosphere and in human clinical specimens, particularly in samples obtained from debilitated patients [1,[4][5][6][7][8][9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…C. metallidurans' ability to act as a PGPR (see the increase in root length at low Cu 2+ levels, Fig. 1), at least in A. thaliana, is not surprising as several members of the Cupriavidus genus and the Burkholderiaceae family are well-known PGPRs or, at least, interact with plants (Gyaneshwar et al, 2011;Bhattacharyya & Jha, 2012;Poupin et al, 2013;Arroyo-Herrera et al, 2020). Because PGPR traits (Zeffa et al, 2020), including 1-aminocyclopropane-1-carboxylate deaminase, auxin phytohormone production, phosphate solubilization, and nitrogen fixation (Bhattacharyya & Jha, 2012;Aeron et al, 2020), have not yet been reported in C. metallidurans, new PGPR traits would be interesting to explore in this bacterium.…”
Section: Discussionmentioning
confidence: 99%